Design, construction and signal processing of a system for analysis of vibrations - del Carpio Salinas, Jorge Alberto (2005)
One of the factors that determine the productivity inside a company is the state of the machinery with which is counted for the production. Our objective was to design a system that allows the engineers to supervise and to evaluate the state of the machinery, so that this in sot only repaired when it doesn't work, but rather one has the possibility to take a periodic registration of the operation of the same one. With it, it'll be possible to identify the flaws of the machinery in their diverse evolutionary phases. This will allow to carry out an appropriate correction of the problem diminishing the maintenance cost and, therefore, to stop the machinery for a smaller period of time. The system that we have designed in compound for a card of acquisition that will allow to capture and to transfer the mechanical vibrations of the machinery toward analysis software that allows the engineers to evaluate and to diagnose the mechanical flaws.